Karya Tari Bakatengkang Terinspirasi Peristiwa Arak Balaki Kabupaten Solok - Wansyah, Andri Syatria; Stevenson, Yan; Wahyuni, Wahida; Emri (JURNAL ILMIAH NUSANTARA, 2025)
The dance work "Bakatengkang" was inspired by a procession event in Nagari Koto Baru, Kubung District, Solok Regency. This event is a tradition of a procession from the house of the induak bako (paternal sister) to the anak pisang or bride in a wedding procession in Solok Regency, Kubung District, Koto Baru Nagari. Usually better known as maantan nasi kuniang from the induak bako to the anak pisang (paternal sister's child). From this event, the artist interpreted it into a dance work, especially about differences of opinion between the bako and anak pisang which were resolved through deliberation and consensus, which was performed at the Auditorium Boestanoel Arifin Adam, Indonesian Institute of the Arts, Padangpanjang. The work, which is divided into three parts, was performed by five male dancers, five female dancers, and ten additional dancers. The costumes used include beautiful stage makeup for female dancers and dashing stage makeup for male dancers. The costumes used are a floral-patterned kuruang dress with loose batik-patterned trousers for women and a Chinese-style guntiang dress for men. The methods used in creating this work include data collection, field observation, data processing, literature review, exploration, improvisation, formation, and evaluation.